Intake of Seeds of Grasses, Shrub and Tree Species by Three Species of Gerbils in Rajasthan Desert - Prakash, Ishwar; Purohit, K. G.; Kametkar, L. R. (Indian Forester, 1967)
Intake by the three gerbils, Meriones hurrianae Jerdon, Tatera indica indica Hardwicke, and Gerbillus gleadowI Murray, of seeds of varioua grass , shrub and tree species, which are of importance as fodder and are used in afforestation and land dune fixation work, was found out and their palatability index has been worked out.Seeds of Cenchrus ciliaris, Eragrostis ciliaris and Erianthus munja are lowly preferred among grasses and those of Acacia species, Azadirachta indica, and Aerva tomentosa among tree and shrub species. If these species of plants are more commonly used for soil conservation work, the damage to seeds by gerbils will be comparatively less than that to other species seeds of which are preferred by the rodents. The consumption of seeds with pulp of Zizyphus nummularia was maximum and they can be used as medium for poison-baiting these rodents.